Cultura laboral y seguridad y prevención de riesgos laborales en el sector industrial de la provincia de Tungurahua. Diseño de un programa de capacitación en seguridad y prevención de riesgos laborales para la gestión formativa de los trabajadores, a través de una consultoría. - Pacheco Venegas, Mario Fermín (2015)
The industrial sector of Tungurahua province is varied and in recent years has had a high organizational and industrial growth, the development and the different production processes have increased occupational risks in workers´ activities. As mentioned above this study is based on the problem identification, based with the basics of the working culture, definitions of the most important security issues and prevention of occupational risks, supported by the current legal basis applicable safety and health developed at work. In order to determine the work culture in the industrial sector of the Tungurahua province, surveys based workers and managers were used at a given sample of the most representative industrial population. When the field study was made, found that there is a deficiency in knowledge on safety and occupational risk prevention in this important sector, so a training program was designed for safety and prevention of occupational risks for management training of workers, which is aims to improve the work culture in prevention of occupational risks to workers and employers, this work culture and proactivity, both workers and employers allow the reduction and elimination of most acts and substandard conditions are important factors contributing to provide safety workplaces it will help in the reduction of accidents and illness in the work.